VESIT Library - An Android Based Application (International Journal of Engineering and Computer Science, 2017)
- In this paper, we present an android mobile application of the VESIT Library system which can help the college students to view all the books available in the college library which is not practically possible by physically looking at each and every book. This system has two major features- first, the user can view the details of his or her issued books and second, the user gets to know about the number of copies of a particular book available in the library. Library database is made on SQL Server 2000. This application accesses the database using the Laravel framework to provide additional security against database hacking. Students use their college Library ID as their login ID. The interface is smooth with minimal lag and and the operations are quick. Basically, this application simplifies the process of visiting the library just to have a look at the books. The technical details are further outlined in this paper.